Classroom Quality and Student Engagement: Contributions to Third-Grade Reading Skills - Guo, Ying; Connor, Carol M.; Tompkins, Virginia; Morrison, Frederick J. (Frontiers in Psychology, 2011)
This study, using NICHD-Study of Early Child Care and Youth Development longitudinal data, investigated the effects of global classroom quality and students’ 3rd grade behavioral engagement on students’ 3rd grade reading achievement (n = 1364) and also examined the extent to which students’ 3rd grade behavioral engagement mediated the association between global classroom quality and children’s’ reading skills. Structural equation modeling (SEM) results revealed that controlling for family sociodemographic risk and students’ 1st grade reading achievement, global classroom quality significantly promote children’s behavioral engagement, which in turn predicts greater reading achievement. Higher level of children’s behavioral engagement was associated with higher reading achievement. Implications for policy and practice were discussed.